Kinematic synthesis of non-clutch mechanical press based on lever mechanism of the third class - V. G. Khomchenko (Омский научный вестник)
The article discusses the kinematic scheme of the lever crank-slider mechanism of the third class, on the basis of which the executive mechanism of a mechanical non-clutch press is proposed under the patent for the invention (RF patent No. 2752399). Switching mode of operation of the press is carried out by moving the control slider from one stationary position to another. The kinematic parameters of the lever mechanism are assigned in such a way that in operating mode the law of motion of the working body of the press is close to the law of motion of the output link of the fourlink central crank-slider mechanism, and in the idle mode — the working body makes small movements (approximate stand) at full rotation of the crank. The analytical dependencies necessary for calculating the mechanism and the corresponding example are given.